PPM BANDENG PRESTO DI KECAMATAN BALONGPANGGANG KABUPATEN GRESIK - ANDRIYANI, NURAINI KUSUMA; Priyantomo, Bayu Aulia; Iswanto, Denny; Rizal Bahri, Muhammad Abu; Sadiyyah, Naila Adinda (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
In Balongpanggang District, Gresik Regency, there is a presto milkfish business which is run directly by Mrs. Suliana. Bu Suliana's presto milkfish is famous for its cheap, five-star taste in the Balongpanggang District area, so Bu Suliana's presto milkfish is in our spotlight as a community empowerment program team at Wijaya Putra University. We see the importance of promoting food products typical of Gresik Regency with additional innovation in delivery and packaging to make them more attractive and increase selling value. The problems experienced by Mrs. Sulianah's pressure milkfish business are limited capital, the milkfish cooler is still in the same place as the vegetables and fruit and she only has one milkfish pressure cooker. So it cannot produce presto milkfish in large quantities. Apart from that, there is a lack of optimizing business opportunities through social media and marketplaces as well as simple business management. In fact, in terms of selling capital and production equipment, it is the most important thing in the business development process. Optimizing marketing and financial management is also no less important so that the business can survive for the future. The assistance solution we offer for business development is providing business development. The method we implement is first, procurement of production support equipment units, in this case cooling machines and pressure cookers as well as vacuum sealer machines for packaging. Second, holding training and direct promotion practice. Third, regular monitoring of sales. We hope that Sulianah's presto milkfish business can develop well, so that it can support the economy of fishermen producing milkfish in Gresik. The outcomes of this PPM program are participating in the proceedings of the PKM CSR conference so that this PPM proposal is published widely so as to provide additional knowledge benefits for society. Apart from that, Ms. Suliah's PPM Milkfish Presto will also be published in online mass media under the media name INews.id.